Redox‐Active Metal Complexes for Anticancer Therapy - Zhang, Pingyu; Sadler, Peter J. (European journal of inorganic chemistry, 2017)
The redox properties of both metals and ligands in transition metal complexes offer unusual routes for new mechanisms of anticancer therapy. Metal complexes can introduce artificial reductive and oxidative stress into cancer cells, including behavior as photoactivatable agents and catalysts. Relatively inert metal complexes (“prodrugs”) can be activated by redox processes within cancer cells. Examples of pharmaceuticals activated by bioreduction include three PtIV and two RuIII compounds that have already entered clinical trials. More recently, novel CoIII, FeIII, PtIV, Ru(III/II), OsII, and IrIII complexes have been reported to exhibit redox‐mediated anticancer activity. Redox activation strategies can introduce new methods to increase cancer cell selectivity and combat drug resistance. Using combination therapy together with redox modulators to increase potency is also possible. This essay focuses on metal complexes that are activated in the reducing environment of cancer cells. Redox reactions in the reducing environment of cancer cells can activate metal complexes so as to deliver bioactive ligands or modulate the redox state of cancer cells. Such redox activation strategies can provide novel mechanisms of action that increase drug selectivity and combat resistance.